2016
DOI: 10.3389/fpsyg.2016.01834
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence and Different Types of Red-Light Behaviors among Cyclists

Abstract: Accident analysis and studies on traffic revealed that cyclists’ violation of red-light regulation is one typical infringement committed by cyclists. Furthermore, an association between cyclists’ crash involvement and red-light violations has been found across different countries. The literature on cyclists’ psychosocial determinants of red-light violation is still scarce. The present study, based on the classification of cyclists’ red-light behavior in risk-taking (ignoring the red-light and traveling through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Moreover, minorities perceived as especially consistent in the advocacy of their views can be especially influential. Social influence processes among road users (Fraboni, Marin Puchades, De Angelis, Prati, & Pietrantoni, 2016) should also be taken into account in future studies on travel behavior and road safety.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, minorities perceived as especially consistent in the advocacy of their views can be especially influential. Social influence processes among road users (Fraboni, Marin Puchades, De Angelis, Prati, & Pietrantoni, 2016) should also be taken into account in future studies on travel behavior and road safety.…”
Section: Resultsmentioning
confidence: 99%
“…Some research findings indicated that the rate of red-light running (RLR) of pedestrians and cyclists was pretty high. In Italy, more than 60% riders were observed to run the red light [2]. Johnson et al [3] investigated 2,061 cyclists and 37.3% of them were reported to have ever run a red light.…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, 11% of cyclist crashes were caused by disobeying a stop sign or a red light [7]. 2 Journal of Advanced Transportation increasing attention of researchers. To improve the safety level of signalized intersections in the city, there is a need to further analyze and summarize the RLR behaviour of pedestrians and cyclists and then propose suggestions on management and control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Second, cyclists did not comply with the legislation. Although there is evidence that a proportion of Italian cyclists do not follow some basic traffic rules such as traffic lights (Fraboni et al, 2016), the number of cyclists that ignored the visibility aids law, and hence the size of the behavior change, is unknown. Drawing from classical deterrence theory (Bates et al, 2012;Fleiter et al, 2013;Homel, 1988), I argue that cyclists may have not complied with the law because the expected costs from violations (e.g., certain, swift, and severe fine sanctions) are perceived lower than the costs of adhering (i.e., having to wear high-vis clothing, which may be considered cumbersome or unfashionable or embarrassing or inconvenient or not having it with you) as well as their gains (e.g., safety).…”
Section: Discussionmentioning
confidence: 99%